2022
DOI: 10.1007/s10668-022-02633-8
|View full text |Cite
|
Sign up to set email alerts
|

Process design and life cycle assessment of furfural and glucose co-production derived from palm oil empty fruit bunches

Abstract: In light of environmental issues, lignocellulosic empty fruit bunch (EFB) biomass is promoted as a carbon–neutral, environmentally friendly, and renewable alternative feedstock. A comprehensive environmental assessment of EFB biorefineries is critical for determining their sustainability in parallel with the bioeconomy policy. Nonetheless, no life cycle assessment (LCA) has been performed on co-producing food and biochemicals (furfural and glucose) derived from EFB biomass. This research is the first to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Applying LCA to glucose production allows for a comprehensive analysis of the environmental footprint and sustainability performance of different production methods. The LCA of glucose production considers the entire life cycle, encompassing various stages such as feedstock acquisition, preprocessing, enzymatic or acid hydrolysis, fermentation, downstream processing, and final product distribution (Ng et al, 2022). It also includes the energy consumption, emissions, and waste generated at each stage.…”
Section: Life Cycle Assessment Of Glucose Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying LCA to glucose production allows for a comprehensive analysis of the environmental footprint and sustainability performance of different production methods. The LCA of glucose production considers the entire life cycle, encompassing various stages such as feedstock acquisition, preprocessing, enzymatic or acid hydrolysis, fermentation, downstream processing, and final product distribution (Ng et al, 2022). It also includes the energy consumption, emissions, and waste generated at each stage.…”
Section: Life Cycle Assessment Of Glucose Productionmentioning
confidence: 99%
“…For glucose production, system boundaries can be set to include the entire production chain, from feedstock acquisition to the production of glucose, or focus on specific stages of the process (Ryan & Yaseneva, 2021). Clearly defining the system boundaries ensures consistency and comparability among different LCA studies and facilitates meaningful interpretation of the results (Ng et al, 2022). During the impact assessment phase of LCA, the collected data on inputs and outputs are translated into environmental impact indicators.…”
Section: Life Cycle Assessment Of Glucose Productionmentioning
confidence: 99%
“…Furthermore, while some studies have focused on specific aspects of the environmental impact of furfural production, comprehensive reports addressing the overall environmental footprints and their implications for human health and ecosystem quality at both the midpoint and endpoint levels are currently lacking. For instance, a study by Raman and Gnansounou [45] evaluated the LCA of bioethanol and furfural production from vetiver leaves, with only carbon dioxide (CO2) emissions and fossil oil depletion considered. Compared with conventional petrol and furfural systems, the results of the LCA indicated that CO2 emissions and fossil oil depletion could be alleviated by 99% and 17%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another research assessed the environmental impact of simultaneous furfural and glucose production from oil palm empty fruit bunch. Four impact categories, i.e., global warming potential (GWP), eutrophication, acidification, and human toxicity, were applied through gate-to-gate LCA [45].…”
Section: Introductionmentioning
confidence: 99%